Development of energy internet based on internet thinking - Jianan LIU; Yanjie DU; Xianyi MENG (Dianxin kexue)
The development of the next internet revolution era energy industry was concerned.Guided by the Maslow’s hierarchy of needs theory，it puts forward the theory of energy development needs was put forward.It was revealed that the energy internet and its very nature generated by the changing of the energy using form has the consistency of the internet thinking.To comply with the development trend of the times，using the internet thinking to build and develop a new generation of smart grid will become the only way of the grid development in the future.